Assessment of heavy metal pollution in seawater, benthic flora and fauna and their ability to survive under stressors along the northern Red Sea, Egypt - Salah-Tantawy Ahmed; Mahdy Aldoushy; Dar Mahmoud A.; Young Shuh-Sen; Abdelreheem Abdelbaset M. A. (Oceanological and Hydrobiological Studies)
The purpose of this study was to assess the north coasts of the Egyptian Red Sea, including Ras Gharieb, Hurghada, Safaga and Qusier, by evaluating the heavy metal pollution in seawater and benthic flora and fauna in the winter and summer of 2016. The concentrations of heavy metals (Fe, Mn, Zn, Cu, Ni, Cd and Pb) were analysed with an atomic absorption spectrophotometer. The results revealed that the Fe levels in the seawater ranged from 7.86 and 27.95 μg l−1, while the Zn concentrations fell between 1.83 and 5.63 μg l−1. In contrast, the recorded values of Mn, Cu, Ni, Pb and Cd in the seawater were minimal at the study sites. Regarding the biota samples, Porifera species were more adaptable than others to an accumulation of most metals in their tissues. Furthermore, seaweeds and seagrasses demonstrated remarkable adaptation in highly polluted regions, especially those with high turbidity, landfilling, sedimentation and high eutrophication rates – much more than the benthic fauna. Our research highlights the critical need for strict regulation of metal emissions in these coastal regions.